2017
DOI: 10.1111/jspn.12185
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ perceptions during the transition to home for their child with a congenital heart defect: How can we support families of children with hypoplastic left heart syndrome?

Abstract: There were limited studies on caregivers' transitions with a child with HLHS, but there also was limited focus on the caregivers' experiences with transitions between hospital and home care for their child with any CHD. Research on the transition experience between hospital care and home care for caregivers of children born with a CHD, and a specific focus on HLHS from the caregivers' viewpoint, would provide insight into the perspective of caregivers during the numerous transitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 13 publications
1
22
0
2
Order By: Relevance
“…Table 4 showed that mother's practice of these activities was had a highly significant difference in all items of care after discharge training compared with before the discharge training, this result in the same line with March. [22] So discharge planning is very effective parts in caring for children after surgery, also should be an important component in the discharge program to ideal outcomes and reduce readmission of children to the hospital with further problems. This is in the agreement with Verhaegh et al [23] As regard to the correlation between mothers' knowledge and their age, and level of education (see Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Table 4 showed that mother's practice of these activities was had a highly significant difference in all items of care after discharge training compared with before the discharge training, this result in the same line with March. [22] So discharge planning is very effective parts in caring for children after surgery, also should be an important component in the discharge program to ideal outcomes and reduce readmission of children to the hospital with further problems. This is in the agreement with Verhaegh et al [23] As regard to the correlation between mothers' knowledge and their age, and level of education (see Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this research are corroborated by the results obtained by researchers who identified anxiety, stress and anxiety among parents of children with congenital heart defects during the transition from hospital to home, especially in view of the need to learn specific medical skills and knowledge. 19 It is important to emphasize the importance of health professionals, especially nurses, to involve the mother in the care given to her child, since during hospitalization, as well as after discharge, the child is seen as a fragile being , existing the insecurity during the moments of providing the necessary care, becoming important the guidance and the follow-up of the health team at this moment. 20 It was noticed in this research that, through effective reception, support and the provision of clear information, with language accessible to these women, the nurse can become a learning facilitator for the dismemberment of care to be performed by them independently.…”
Section: Certainly Not But I Know I'm Going To Have To Learn Why Whmentioning
confidence: 99%
“…Lisanti and colleagues found an association between mothers’ perceptions of altered parental role in the cardiac intensive care unit (CICU) and maternal anxiety (19). A recent literature review of common stressors during the transition from hospital to home for parents of children with CHD found that feeding problems, difficulties bonding, and a lack of confidence in one’s own ability to care for a medically complex child were critical challenges (20). No prior studies have comprehensively examined the experiences of mothers and fathers of young children with CHD from diverse backgrounds from the time of CHD diagnosis through discharge to home after cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%